Aluminum and Magnesium Metal Matrix Nanocomposites - Ceschini, Lorella; Dahle, Arne; Gupta, Manoj; Jarfors, Anders Eric Wollmar; Jayalakshmi, S.; Morri, Alessandro; Rotundo, Fabio; Toschi, Stefania; Singh, R. Arvind (Springer Singapore : Imprint: Springer, 2017)
The book looks into the recent advances in the ex-situ production routes and properties of aluminum and magnesium based metal matrix nanocomposites (MMNCs), produced either by liquid or semi-solid state methods. It comprehensively summarizes work done in the last 10 years including the mechanical properties of different matrix/nanoreinforcement systems. The book also addresses future research direction, steps taken and missing developments to achieve the full industrial exploitation of such composites. The content of the book appeals to researchers and industrial practitioners in the area of materials development for metal matrix nanocomposites and its applications.
Keywords: Materials science.; Structural materials.; Nanotechnology.; Metals.; elektronické knihy; electronic books